Comparison of ball-and-racquet impact force between two tennis backhand stroke techniqes - Wu, S. K.; Gross, M. T.; Prentice, W. E.; Yu, B. (Journal of Orthopaedic & Sports Physical Therapy, 2001)
STUDY DESIGN: A mixed design for kinetic comparison of 2 types of one-handed backhand strokes and 2 skill levels in tennis. OBJECTIVES: To develop and evaluate a model to estimate the impact force on the racquet during tennis stroke, and to compare the peak impact force between one-handed backhand stroke with a long backswing and one-handed backhand stroke with a short backswing and between the beginning and advanced players. BACKGROUND: A one-handed backhand stroke is commonly used in tennis and may be associated with many upper extremity over-use injuries. An understanding of kinetics of the backhand stroke is essential for understanding injury mechanisms and prevention. METHODS AND MEASURES: Five male advanced tennis players and 4 male and 1 female beginning tennis players participated. Mean age was 32.2 +/- 7.0 years. Each subject was instructed to use the 2 types of one-handed backhand strokes to hit balls from a tennis ball machine. Three-dimensional coordinates of critical body and racquet landmarks were obtained. A mathematical model was developed to estimate the contact duration and the peak impact force during a stroke. RESULTS: The estimated peak impact forces were reproducible and comparable to those reported in the literature from direct measurements. A one-handed backhand stroke with a short backswing had a significantly shorter contact duration (0.008 +/- 0.003 seconds) and a greater peak resultant impact force (330.0 +/- 140.7) than that with a long backswing (0.016 +/- 0.004 seconds and 180.8 +/- 49.1 N). Skill level did not significantly affect the peak resultant impact force. CONCLUSION: A long backswing in a one-handed backhand stroke may reduce the load on the upper extremity and may assist in reducing the risks of tennis-related upper extremity over-use injuries.